2018
DOI: 10.1093/sleep/zsy189
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation enhances inter-stimulus interval effect on vigilant attention performance

Abstract: Study Objective: Sleep deprivation significantly reduces the ability to maintain a consistent alertness level and impairs vigilant attention. Previous studies have shown that longer inter-stimulus interval (ISI) are associated with faster reaction times (RTs) on the Psychomotor Vigilance Test (PVT). However, whether and how sleep deprivation interacts with this ISI effect remains unclear. Methods: N = 70 healthy adults (age range 20-50 years, 41 males) participated in a 5-day and 4-night in-laboratory controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
1
19
0
2
Order By: Relevance
“…In the present study, PVT results showed that the LSQ group had significantly slower RTs than did the HSQ group. These results are consistent with those of Yang et al (2018), who indicated that sleep deprivation increased RT and reduced processing speed and attention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, PVT results showed that the LSQ group had significantly slower RTs than did the HSQ group. These results are consistent with those of Yang et al (2018), who indicated that sleep deprivation increased RT and reduced processing speed and attention.…”
Section: Discussionsupporting
confidence: 92%
“…Drummond et al (1999) used fMRI to examine arithmetic performance and cerebral activation after sleep deprivation and found decreased prefrontal cortex responsiveness in sleep-deprived participants. Participants with low sleep quality (LSQ) exhibited longer RTs in performance tests of vigilant attention (Yang et al, 2018). Researchers also reported that a sleep deprivation-induced reduction in the phonological and visuospatial components of the working memory (del Angel et al, 2015) was associated with cognitive impairment and reduction in the speed of processing information (Waters & Bucks, 2011).…”
mentioning
confidence: 99%
“…Participants. A total of 70 healthy adults (age range 21-50 years, 41 males) participated in a 5-day and 4-night in-laboratory controlled sleep deprivation experiment 93,94 , including 54 adults in the experimental group with one night of TSD ( Fig. 1a) and 16 adults in the control group without sleep loss (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The PVT is a widely used neurobehavioral test and is a sensitive measure of fatigue and attention deficits in clinical and experimental contexts [22,23]. Performance on psychomotor vigilant attention tasks generally improves with increased physiological arousal [24].…”
Section: Discussionmentioning
confidence: 99%